608. INCIDENCE AND IMPACT OF PREOPERATIVE HIATAL HERNIA IN PATIENTS WITH ESOPHAGEAL CARCINOMA UNDERGOING CURATIVE SURGICAL RESECTION. (24th September 2022) - Solomon, Daniel; Zaslavsky, Adi; Varon, Danielle; Israeli, Tal; Amlinsky, Yelena; Tamir, Shlomit; Kashtan, Hanoch
Abstract: Hiatal hernia (HH) and gastroesophageal reflux disease (GERD) are risk factors for esophageal adenocarcinoma. High positive margin rates and poor survival were previously described among HH patients undergoing esophagectomy. We sought to describe incidence and impact of HH on outcomes following esophagectomy in a population of patients undergoing predominantly cervical anastomosis. Patients who underwent esophagectomy 2012-2019 for esophago-junctional carcinoma were included. CT studies were blindly reviewed by two radiologists. A third radiologist reviewed cases of disagreement. Hernias >3 cm were included in the HH group. Overall, 66 patients (33%) had HH >3 cm. The control group included 12 patients (6%) with <3 cm HH and 106 (53%) without HH. Patients with HH had higher Charlson Comorbidity Index (CCI) (p=0.017). Location of anastomosis was similar among cohorts (cervical anastomosis 82.2% vs 92.4%, p=0.113). HH patients had higher incidence of atrial dysrhythmia (16.7% vs 5.1% p=0.015). Rates of R0 resections were similar (95.8% vs 93.9%, p=0.724). Subgroup analysis on adenocarcinoma patients confirmed higher rates of signet ring cell features among HH patients (28.6% vs 12.3%, p=0.034). HH was not associated with poor disease free survival (p=0.274). Patients with preoperative HH had higher CCI, higher rates of postoperative atrial dysrhythmias and signet ring cell features on pathology. In a population with predominant cervical anastomosis, positive margin rates were low and survival comparable among cohorts.